Possession, projection, and individuation a study of Lillian Beye in Anais Nin's Ladders to Fire and Seduction of the Minotaur - Mabitad, Armida Amparo B.; Aureus, Carlos O. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 1994)
Lillian Beye is a female archetype in Anais Nin's continuous novel, Cities of the Interior. Lillian typifies the unfulfilled woman who is always at odds with herself. Because she cannot accept the negative aspects of her personality, she suffers in Ladders to Fire from two Jungian complexes: possession and projection. In the possession complex, Lillian fails to control her unconscious urge to "possess," or own, every person she involves herself with (e.g. Djuna, Jay, Sabina, etc.). Thus, her relationships, whether heterosexual or homosexual, are terminated by her destructive, possessive behavior. The author traces the possession-complex's roots in the latter complex: projection. Since Lillian is not satisfied with her inward nor her outward self, she seeks an object with which she may displace, or "project," her emotions. In doing this, she assimilates the person's psychological and physical countenance and, in turn, projects it inward, thereby causing her breakdown at the end of Ladders to Fire. Lillian's defense mechanisms apparently do not work. The possession-complex arises afterwards, in order for Lillian to keep the object of her projection-complex attached to herself; and again, she tries to own the person. Thus, continues the cycle of the possession-projection complex in Lillian's psyche. Lillian transcends these complexes in Seduction of the Minotaur. While taking a vacation in Golconda, Mexico, Lillian meets two father-figures: Dr. Hernandez and Hatcher. Both represent respectively the positive and negative sides of her personality. Her travels and dialogues with them bring back memories, which compel her to re-evaluate her childhood and adult life prior to her visit to Mexico. After which, she learns to integrate her childhood with the present, to resolve the conflict between the positive and negative aspects of her personality, and to reconcile her rational capacities with her instinctive impulses. Thus, she achieves the state of individuation, or the realization of the self. Using the French/Psychoanalytic Feminist perspective, this study examines the search for the self as a woman, conveyed in Anais Nin's Ladders to Fire and Seduction of the Minotaur, throught the character Lillian. The search for an identity of the woman is an integral component of the Feminist discourse. To Anais Nin, the self is the core of all human existence. This thesis addresses this still inconclusive issue.
Thesis (B.A. in English Studies : Anglo-American Literature)--University of the Philippines Diliman
Includes bibliographical references and appendices.